Beneficial Modulation of Lipid Mediator Biosynthesis in Innate Immune Cells by Antirheumatic Tripterygium wilfordii Glycosides - Kehong Zhang; Simona Pace; Paul M. Jordan; Lukas K. Peltner; Alexander Weber; Dagmar Fischer; Robert K. Hofstetter; Xinchun Chen; Oliver Werz (Biomolecules, 2021)
Tripterygium wilfordii glycosides (TWG) is a traditional Chinese medicine with effectiveness against rheumatoid arthritis (RA), supported by numerous clinical trials. Lipid mediators (LM) are biomolecules produced from polyunsaturated fatty acids mainly by cyclooxygenases (COX) and lipoxygenases (LOX) in complex networks which regulate inflammation and immune responses and are strongly linked to RA. The mechanism by which TWG affects LM networks in RA treatment remains elusive. Employing LM metabololipidomics using ultra-performance liquid chromatography-tandem mass spectrometry revealed striking modulation of LM pathways by TWG in human monocyte-derived macrophage (MDM) phenotypes. In inflammatory M1-MDM, TWG (30 µg/mL) potently suppressed agonist-induced formation of 5-LOX products which was confirmed in human PMNL and traced back to direct inhibition of 5-LOX (IC50 = 2.9 µg/mL). TWG also efficiently blocked thromboxane formation in M1-MDM without inhibiting other prostanoids and COX enzymes. Importantly, in anti-inflammatory M2-MDM, TWG (30 µg/mL) induced pronounced formation of specialized pro-resolving mediators (SPM) and related 12/15-LOX-derived SPM precursors, without COX and 5-LOX activation. During MDM polarization, TWG (1 µg/mL) decreased the capacity to generate pro-inflammatory 5-LOX and COX products, cytokines and markers for M1 phenotypes. Together, suppression of pro-inflammatory LM but SPM induction may contribute to the antirheumatic properties of TWG.